2020
DOI: 10.1016/j.pec.2020.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Parental expectations of raising a child with disability in decision-making for prenatal testing and termination of pregnancy: A mixed methods study

Abstract: This is a repository copy of Parental expectations of raising a child with disability in decision-making for prenatal testing and termination of pregnancy: A mixed methods study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Some believe that raising a child with a disability will be a less rewarding experience than raising an able-bodied child (109). Having a disabled child can be considered a disruption to the "natural order" (68, p. 4) or a burden on the family and can raise concerns about financial security (84,109). It can also be seen as a failure to meet cultural expectations related to parental obligations (68) or to meet social norms related to being a good mother (7,68).…”
Section: Mainland Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…Some believe that raising a child with a disability will be a less rewarding experience than raising an able-bodied child (109). Having a disabled child can be considered a disruption to the "natural order" (68, p. 4) or a burden on the family and can raise concerns about financial security (84,109). It can also be seen as a failure to meet cultural expectations related to parental obligations (68) or to meet social norms related to being a good mother (7,68).…”
Section: Mainland Chinamentioning
confidence: 99%
“…Termination of pregnancy for medical reasons is common and seen as less morally complex than it is in the Western context (84,109). In both China and Hong Kong, terminations of pregnancies diagnosed with abnormal chromosomal aneuploidies are common (81,171).…”
Section: Mainland Chinamentioning
confidence: 99%
“…Furthermore, women feel a sort of social pressure in so far as they consider the risk assessment compulsory and they perceive the responsibility of doing the right thing ( Ngan et al, 2020 ; Salema et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…As several studies have shown, the choice of prenatal testing involves the couple and rarely external elements ( Laberge et al, 2019 ; Nazaré et al, 2011 ). However, the social pressure felt by women, who often interpret prenatal testing as part of pregnancy routine without a real conscious choice, should not be underestimated ( Ngan et al, 2020 ; Salema et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is a delicate question and difficult to answer, as one can only hypothesise from their current situation in that moment what their response will be. This response may change during different stages of life and be influenced by their parenting experience and indirect experience of other parents who have children with disabilities [16].…”
Section: Introductionmentioning
confidence: 99%